Nancy Drew. Season two [videorecording (DVD)] - Landau, Noga; Schwartz, Josh, 1976-; Savage, Stephanie (CBS, 2021)
Nancy Drew is a brilliant teenage detective whose sense of self had come from solving mysteries in her hometown of Horseshoe Bay, Maine, until her mother's untimely death derails Nancy's college plans.